SINERGITAS KONSEP MAQASHID AL-SYARIAH DENGAN REALISASI WISATA DI KABUPATEN BONE - Ismail Ismail; Nur Amal Mas (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2022)
This study discusses the concept of maqashid Al Syariah in the realm of tourism in Bone Regency. The concept of maqashid Al-Syariah aims to preserve nature and the balance of human life which is the need for daruriyah in the form of maintaining religion, protecting offspring, maintaining reason, protecting souls and protecting property. This study aims to describe a reference for the community in traveling. This research is a field research or uses a qualitative approach that emphasizes the description of the object under study. The results of the study show that the concept of maqashid Al Syariah is very strong in synergy with tourism and complements each other in achieving goals based on the following aspects: (1) Categorization of tourist attractions; (2) management of tourist attractions; (3) Types of tourist attractions; (4) Starting the journey with intention; (5) Physical and spiritual satisfaction; (6) Science tourism; (7) Tourism is part of alms; (8) Symbiotic mutualism; (9) Children's study and play room; (10) forms of self-refraction of the keywords maqashid Al-Syariah tourism synergy.